REPRESENTASI KONFLIK SOSIAL DALAM FILM OMAR 2013 KARYA HANY ABU-ASSAD (SOSIOLOGI SASTRA) - Adya Wijaya, Naufal; Ainusyamsi, Fadlil Yani; Rohanda, Rohanda ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2025)
This research analyzes the representation of social conflict in the film "Omar" (2013) by Hany Abu-Assad through a literary sociology approach. This film depicts the life of a young Palestinian who is trapped between his personal aspirations and the political realities that limit him. Using qualitative analysis methods, this research explores the main themes that emerge in the narrative, characters and settings that reflect social and political dynamics in conflict zones. This study finds that “Omar” not only tells an individual story but also reflects the collective experience of the Palestinian community oppressed by the occupation. Through complex characters, the film depicts shifting identities, loyalties, and the struggle for freedom. These findings demonstrate that “Omar” serves as an effective medium for understanding and reflecting on deep social conflicts, as well as the challenges individuals face in a broader context. Therefore, this research contributes to the field of literary sociology by highlighting how art can provide a deeper understanding of social and political reality.